2022
DOI: 10.1016/j.ejca.2021.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Third dose of anti-SARS-CoV-2 vaccine for patients with cancer: Should humoral responses be monitored? A position article

Abstract: Taking into account higher risk of severe coronavirus disease 2019 (COVID-19) or death among patients with cancer, as well as impaired immunogenicity following anti-SARS-CoV-2 vaccines, in addition to waning immunity, booster dosing appears mandatory in this patient population. This review sought to provide reasonable evidence so as to assist oncologists in their daily practice, helping them decide when an anti-SARS-Cov2 antibodies (Abs) dosage should be scheduled following a full two-dose vaccination and if n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 84 publications
5
44
1
1
Order By: Relevance
“…Patients with cancer are at a significantly increased risk of severe morbidity and mortality from coronavirus disease of 2019 (COVID-19) [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. In a previous report, we showed that an adequate antibody response was achieved after two doses of BNT162b2, but not after one, in patients with cancer vaccinated during anticancer therapy, and at lower seropositivity rates compared with healthy controls [ 10 ], in accordance with additional reports [ [11] , [12] , [13] , [14] , [15] ]. Conflicting data came from follow-up studies showing that seropositivity rates among patients with cancer compared with healthy controls were lower at four months after the second vaccine dose [ 16 ], but were similar at six months [ 17 ].…”
Section: Introductionsupporting
confidence: 90%
“…Patients with cancer are at a significantly increased risk of severe morbidity and mortality from coronavirus disease of 2019 (COVID-19) [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. In a previous report, we showed that an adequate antibody response was achieved after two doses of BNT162b2, but not after one, in patients with cancer vaccinated during anticancer therapy, and at lower seropositivity rates compared with healthy controls [ 10 ], in accordance with additional reports [ [11] , [12] , [13] , [14] , [15] ]. Conflicting data came from follow-up studies showing that seropositivity rates among patients with cancer compared with healthy controls were lower at four months after the second vaccine dose [ 16 ], but were similar at six months [ 17 ].…”
Section: Introductionsupporting
confidence: 90%
“…The occurrence of COVID-19 after the booster dose in a sizeable proportion of cancer patients on active therapy requires attention, and needs to be further explored in large series investigated by international consortia. Nevertheless, the usefulness of a third vaccine dose in cancer patients seems to remain unquestionable at present ( 20 , 21 , 22 , 23 , 24 ), also due to the observed increase of neutralizing antibodies to the Omicron variant ( 10 , 11 , 12 ), and to the generally mild clinical course of SARS-CoV-2 infection we observed, complying with the aim of vaccination to reduce COVID-19-related hospitalizations and deaths. Consistently, the booster dose was reported to significantly associate with lower rates of symptomatic infections in healthy subjects compared to those who received only two vaccine doses ( 13 ).…”
Section: Discussionsupporting
confidence: 71%
“…After the second vaccine dose, only one serological non-responder was found (0.3%). In the literature, non-responders are described in patients with immune deficiencies [ 38 , 39 , 40 ]. We found no study that investigated non-responders in HW.…”
Section: Discussionmentioning
confidence: 99%